Hemangioma of the umbilical cord with associated amnionic inclusion cyst: two uncommon entities occurring simultaneously - V.V., A.A. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Errata PATHOLOGICA 2019;111:13-17; DOI:10.32074/1591-951X-26-17 Hemangioma of the umbilical cord with associated amnionic inclusion cyst: two uncommon entities occurring simultaneously G. Angelico1, S. Spadola1, A. Ieni3, A. Gurrera4, M.G. Arena5, S.G. Vitale6, D. Arciuolo1, M. Valente1, A. Santoro1, F. Inzani1, G.F. Zannoni1,2 1 Department of Gynecologic Pathology, Fondazione Policlinico Universitario A. Gemelli, IRCCS, Rome, Italy; 2 Department of Gynecologic Pathology, Fondazione Policlinico Universitario A. Gemelli, IRCCS, Università Cattolica del Sacro Cuore, Rome, Italy; 3 Department of Human Pathology in Adult and Developmental Age “Gaetano Barresi”, Unit of Pathological Anatomy, University of Messina, AOU Policlinico G. Martino, Messina, Italy; 4 Division of Pathology, Vittorio Emanuele, University Hospital “Policlinico-Vittorio Emanuele”, University of Catania, Italy; 5 Department of Obstetrics & Gynecology, University of Catania, Italy; 6 Unit of Gynecology and Obstetrics, Department of Human Pathology in Adulthood and Childhood “G. Barresi”, University of Messina, Italy Corrige PATHOLOGICA 2019;111:13-17; DOI:10.32074/1591-951X-26-17-EC Hemangioma of the umbilical cord with associated amnionic inclusion cyst: two uncommon entities occurring simultaneously G. Angelico1, S. Spadola1, A. Ieni3, A. Gurrera4, M.G. Arena5, D. Arciuolo1, M. Valente1, A. Santoro1, F. Inzani1, G.F. Zannoni1,2 1 Department of Gynecologic Pathology, Fondazione Policlinico Universitario A. Gemelli, IRCCS, Rome, Italy; 2 Department of Gynecologic Pathology, Fondazione Policlinico Universitario A. Gemelli, IRCCS, Università Cattolica del Sacro Cuore, Rome, Italy; 3 Department of Human Pathology in Adult and Developmental Age “Gaetano Barresi”, Unit of Pathological Anatomy, University of Messina, AOU Policlinico G. Martino, Messina, Italy; 4 Division of Pathology, Vittorio Emanuele, University Hospital “Policlinico-Vittorio Emanuele”, University of Catania, Italy; 5 Department of Obstetrics & Gynecology, University of Catania, Italy Acknowledgements The authors are grateful for the insightful suggestions provided by Dr. Salvatore Giovanni Vitale, which have contributed to improve the manuscript.